To convert the given quadratic function to standard form, we can first expand the equation:
y = (x + 3)^2 - 5
y = (x + 3)(x + 3) - 5
y = x^2 + 6x + 9 - 5
y = x^2 + 6x + 4
Now we can identify the values of a, b, and c in standard form y = ax^2 + bx + c:
a = 1
b = 6
c = 4
Therefore, the values of a, b, and c for the quadratic function y = (x + 3)^2 - 5 in standard form are:
a = 1
b = 6
c = 4
Convert the following quadratic function to standard form y = ax^2 + bx + c and identify the values of a, b, and c.
y = (x + 3)^2 - 5
a =
b =
c =
1 answer